Impact of tumor size and nodal status on recurrence of nonfunctional pancreatic neuroendocrine tumors ≤2 cm after curative resection: A multi‐institutional study of 392 cases. Issue 7 (30th September 2019) - Dong, Ding‐Hui; Zhang, Xu‐Feng; Poultsides, George; Rocha, Flavio; Weber, Sharon; Fields, Ryan; Idrees, Kamran; Cho, Cliff; Maithel, Shishir K.; Pawlik, Timothy M.; ,
Abstract: Background: The current study sought to define the impact of lymph node metastasis (LNM) relative to tumor size on tumor recurrence after curative resection for nonfunctional pancreatic neuroendocrine tumors (NF‐pNETs) ≤2 cm. Methods: Patients who underwent curative resection for ≤2‐cm NF‐pNETs were identified from a multi‐institutional database. Risk factors associated with tumor recurrence as well as LNM were identified. Recurrence‐free survival (RFS) was compared among patients with or without LNM. Results: A total of 392 ≤2‐cm NF‐pNETs patients were identified. Among the 328 patients who had lymph node dissection and evaluation, 42 (12.8%) patients had LNM. LNM was associated with tumor recurrence (hazard ratio, 3.06; P = .026) after surgery. RFS was worse among LNM vs no LNM patients (5‐year RFS, 81.7% vs 94.1%; P = .019). Patients with tumors measuring 1.5‐2 cm had a two‐fold increase in the incidence of LNM vs patients with tumors <1.5 cm (17.9% vs 8.7%, odds ratio, 2.59; P = .022), as well as a higher risk of advanced tumor grade and higher Ki‐67 levels (both P < .01). After curative resection, a total of 14 (8.0%) patients with a tumor of 1.5‐2 cm and 10 (4.5%) patients with tumor <1.5 cm developed tumor recurrence. Conclusion: Surgical resection with lymphadenectomy should be considered for patients with NF‐pNETs ≥1.5‐2.0 cm.